A diffraction-limited laser of 25/400 Yb3+/Al3+/P5+/F− silica fiber with a zigzag refractive index profile. (31st July 2017) - Lin, Zhiquan; Lou, Fengguang; Wang, Meng; Zhang, Guodong; Zhang, Lei; Feng, Suya; Yu, Chunlei; Chen, Danping; Hu, Lili
Abstract: In this work, a Yb 3+ /Al 3+ /P 5+ /F − co-doped low-NA preform with larger than 0.4 wt.% Yb 3+ doping concentration and zigzag refractive index profile was fabricated based on solution doping modified chemical vapor deposition technology. The modality of the preform refractive index profile was simulated based on a circle-symmetry-distribution fiber model. According to the simulation results a step-index 25/400 double cladding fiber with core NA of ~0.04 was drawn. Pumped with a 970 nm laser diode, a diffraction-limited oscillator-laser output with ~71% slope efficiency and M 2 of ~1.06 were achieved at bending diameter  ⩾50 cm after stripping cladding light. For bending diameters less than 50 cm, the laser efficiency measured at stripping cladding light decreases with decrease in bending diameter.